Trade-off between thermal preference and sperm maturation in a montane lizard. (April 2023) - Quintero-Pérez, Rosa Isela; Méndez-de la Cruz, Fausto Roberto; Miles, Donald B.; Vera Chávez, Mirna Crizel; López-Ramírez, Yolanda; Arenas-Moreno, Diego Miguel; Arenas-Ríos, Edith
Abstract: Temperature is a key abiotic factor that influences performance of several physiological traits in ectotherms. Organisms regulate their body temperature within a range of temperatures to enhance physiological function. The capacity of ectotherms, such as lizards, to maintain their body temperature within their preferred range influences physiological traits such as speed, various reproductive patterns, and critical fitness components, such as growth rates or survival. Here, we evaluate the influence of temperature on locomotor performance, sperm morphology and viability in a high elevation lizard species ( Sceloporus aeneus ). Whereas maximal values for sprint speed coincides with field active and preferred body temperature, short-term exposure at the same range of temperatures produces abnormalities in sperm morphology, lower sperm concentration and diminishes sperm motility and viability. In conclusion, we confirmed that although locomotor performance is maximized at preferred temperatures, there is a trade-off with male reproductive attributes, which may cause infertility. As a consequence, prolonged exposure to preferred temperatures could threaten the persistence of the species through reduced fertility. Persistence of the species is favored in environments with access to cooler, thermal microhabitats that enhance reproductive parameters. Highlights: Preferred temperature improve locomotor performance, but decreases sperm parameters of the lizard Sceloporus aeneus . Locomotor performance is maximized when the body temperature approaches the species' preferred temperature (32 °C). Exposure to temperatures (24 °C and 28 °C), below the preferred temperature (32.7 °C), enhances sperm parameters.